Continuous Monitoring Analysis of Rice Quality in Southern China Based on Random Forest - Lin Lu; Bo Zeng; Shihua Yang; Mingxue Chen; Yonghong Yu (Journal of Food Quality)
Rice quality has received more attention, so monitoring and analysis are of great significance to rice quality. General quality indexes of rice in southern China from 2011 to 2020 were determined, including processing quality (brown rice yield, milled rice recovery, head rice yield), appearance quality (grain length, length-width ratio, chalky rice percentage, chalkiness degree, transparency), and cooking quality (alkali spreading value, gel consistency, amylose). Principal component analysis was used to distinguish the regional quality of southern rice. The results showed that amylose and chalkiness were the main contributory quality indexes of rice in South China, the upper reaches of the Yangtze River, and the middle and lower reaches of the Yangtze River. In the past decade, the total high-quality rate of rice in the South has improved. The random forest was used to determine the important influence index of rice quality. The results showed that chalkiness degree, alkali spreading value, and gel consistency were important indexes affecting the quality of southern rice, and random forest could be used as an effective approach for continuous monitoring and analysis of rice quality.